2018
DOI: 10.1039/c8ra02314j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the electro-mechanical properties of polydimethylsiloxane elastomers through blending with poly(dimethylsiloxane-co-methylphenylsiloxane) copolymers

Abstract: In this work, improved electro-mechanical properties of silicone-based dielectric elastomers are achieved by means of adding so-called "voltage-stabilisers" prepared from phenyl-functional copolymers prepared using oxyanionic ring-opening polymerisation of octamethylcyclotetrasiloxane (D4) and either tetramethyltetraphenylcyclotetrasiloxane (T4) or octaphenylcyclotetrasiloxane (O4). The concentration of the voltage stabiliser was varied both by changing the molar ratio between methyl and phenyl groups in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 63 publications
(68 reference statements)
2
17
0
Order By: Relevance
“…Thereby, the increased dielectric permittivity is ascribed to the combined usage of ILB and glycerol. [36][37] According to Equation (2), the 100% increase in dielectric permittivity of S184-gly-ILB-5% is beneficial, in that it increases the Fom(DEA) of transducers. Variations in dielectric losses are presented in Figure 5.…”
Section: Dielectric Properties and Conductivitymentioning
confidence: 99%
“…Thereby, the increased dielectric permittivity is ascribed to the combined usage of ILB and glycerol. [36][37] According to Equation (2), the 100% increase in dielectric permittivity of S184-gly-ILB-5% is beneficial, in that it increases the Fom(DEA) of transducers. Variations in dielectric losses are presented in Figure 5.…”
Section: Dielectric Properties and Conductivitymentioning
confidence: 99%
“…resulting in increased relative permittivity and electrical breakdown strength compared to control elastomers, while retaining a low dielectric loss, thus evidencing their efficiency as voltage stabilizers. 29 In a previous work, we used trialkoxysilanes having different organic groups attached to the silicon atom (methyl, phenyl, aminopropyl, chloropropyl and cyanopropyl) in excess as crosslinking agents for polydimethylsiloxane-α,ω-diols and precursors for in situ formation of silsesquioxane (SSQ) domains. It was found that the elastomers crosslinked with the phenyl derivative had significant lower values for dielectric losses compared to similar elastomers with cyan groups.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric energy harvesters can provide sustainable energy from the ambient sources, such as ocean waves [8,9,10,11,12] and human motion [13,14], but their efficiency and economic profitability is dependent, among others, on the material-related losses of the elastomeric membrane. Silicone rubber is often used for dielectric energy harvesting, as it possesses low dielectric losses, low mechanical hysteresis, dynamic damping and stress relaxation [15,16]. However, a modification of the material is needed in order to increase the economic profitability of elastomer-based energy harvesters [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, a modification of the material is needed in order to increase the economic profitability of elastomer-based energy harvesters [17]. A modification of the silicone matrix by covalent attachment of various molecules can not only improve mechanical properties of the material, but also result in lower dielectric losses and better electrical breakdown resistance in dielectric elastomer transducers [16]. Therefore, it is expected that the introduction of NDs into a silicone matrix improves the physical and chemical interactions within the matrix.…”
Section: Introductionmentioning
confidence: 99%